(Pro)renin receptor aggravates myocardial pyroptosis in diabetic cardiomyopathy through AMPK-NLRP3 pathway - Li, Shengnan; Zhang, Jingjing; Zhao, Yuewen; Kang, Li; Jie, Haipeng; Dong, Bo (Frontiers in Pharmacology, 2024)
As one of the most common complications of diabetes, diabetic cardiomyopathy (DCM) is the main cause of heart failure in patients with diabetes. (Pro) renin receptor (PRR) is a member of renin angiotensin aldosterone system (RAAS). Its activation can not only promote the production of angiotensin I, but also trigger many intracellular signaling pathways independent of Ang Ⅱ. Previous studies have shown that PRR can participate in a variety of disease processes. The purpose of this study was to investigate whether PRR is involved in diabetic myocardial pyroptosis mediated by NLRP3 inflammasome. We established diabetic rats model by intraperitoneal injection of streptozotocin (STZ). Primary cardiomyocytes were stimulated with high glucose and PRR overexpression or PRR knockdown was achieved by adenovirus transfection. We found that overexpression of PRR could stimulate the activation of NLRP3 inflammasome, aggravate diabetic myocardial pyroptosis, and aggravate cardiac dysfunction in DCM. On the contrary, PRR knockdown can alleviate the level of myocardial pyroptosis in DCM and improve cardiac function. The related mechanism was that PRR could inhibit AMPK phosphorylation and promote the activation of NLRP3 inflammasome. In conclusion, the overexpression of PRR may aggravate myocardial pyroptosis in DCM through AMPK-NLRP3 pathway.